The stone moved: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The Stone Moved" is a story that illustrates themes of faith, perseverance, and divine intervention. It often centers around a character facing seemingly insurmountable challenges symbolized by a heavy stone. Through unwavering belief and effort, the character finds that the stone moves, representing the idea that with faith and determination, obstacles can be overcome. The narrative encourages hope and the understanding that help can come in unexpected ways.